Bishop Juraj Strossmayer, Izidor Kršnjavi and the Foundation of the Chairs in Art History and Ancient Classical Archaeology at Zagreb University - Damjanović, Dragan (Array, 2009)
The discipline of art history in Croatia in the 19th, and almost the entire first half of the 20th century was closely connected to art history in Vienna, the education center of the Habsburg Monarchy, and in particular to the work of Rudolf Eitelberger von Edelberg. Due to his influence, the year 1877/1878 saw the foundation of the Chair in Art History and Ancient Classical Archaeology at Zagreb University. The chair would later develop into the Departments of Art History and Archaeology at the Zagreb Faculty of Philosophy (the original name of the present Faculty of Humanities and Social Sciences), an institution which was to have a major educational role in the field of art history and archaeology in Croatia. The driving force for its establishment came from Bishop Josip Juraj Strossmayer and the first academically trained art historian, Izidor Kršnjavi. The motives behind their decision to establish the chair as well as the problems they encountered in the process form the topic of this paper.